Analisis Perbandingan Efektivitas Pembelajaran Daring & Luring Terhadap Pemahaman Mahasiswa Di Palangka Raya - Selsa Nandini; Olivia Olivia; Melysha Pratiwi; Imelia Nurazizah; Angel Safitri; Nabilla Syahvalensi; Bhayu Rhama (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
This study aims to analyze and compare the effectiveness of online (daring) and offline (luring) learning on students’ understanding in Palangka Raya. A quantitative approach with a comparative descriptive design was employed. Data were collected using a five-point Likert-scale questionnaire consisting of 20 statements—ten related to online learning and ten related to offline learning—distributed to 110 students as respondents. The reliability test produced a Cronbach’s Alpha of 0.945, indicating that the research instrument has excellent internal consistency. Descriptive analysis revealed an average score of 3.58 (SD = 0.897) for online learning and 3.81 (SD = 0.873) for offline learning, both of which fall into the high category. A Pearson correlation test showed a strong, significant, and positive relationship between students’ perceptions of online and offline learning (r = 0.619; p < .001). A paired sample t-test indicated a significant difference between the effectiveness of online and offline learning (t = -3.148; df = 109; p = .002), with offline learning obtaining a significantly higher mean score. These findings suggest that offline learning is perceived as more effective than online learning in enhancing student understanding, particularly in terms of interaction, focus, and motivation. Nevertheless, online learning remains advantageous in terms of time flexibility and learning autonomy, so that a combination of both methods (blended learning) may serve as a more optimal learning strategy.